Updated Management of Ulcerative Colitis - Prabowo, Muhamad Reza; Fauzi, Achmad (The Indonesian Society for Digestive Endoscopy, 2025)
Ulcerative Colitis (UC) is a chronic disorder of Inflammatory Bowel Disease (IBD) which showed pathological changes of mucosa (symmetrical, diffuse) that involving rectum and may be extended to proximal colon. In general, target of the treatment quite indistinguishable to Crohn’s Disease (CD), such as improving quality of life, treating the acute condition, maintaining remission status, preventing complications, and achieving adequate nutritional status. Nowadays, there are so many therapeutic agents which were more effective than previous drugs. Another reason we should have left prior medicine is the safety of newer agents are promising. Today’s technology advances make gastroenterologist easier to give more treatment choice to every spectrum of ulcerative colitis. This review aims to provide an updated overview of ulcerative colitis management.